Psyhological Adjustment Effectivity in Elder Siblings of Children with Down Syndrome - Santoso, Devina Kurniawan; Handayani, Penny (Indonesian Journal of Disability Studies, 2018)
Elder siblings play an important role in the family such as being a replacement caregiver for the children with Down syndrome. Therefore, they need an effective psychological adjustment to fulfill the responsibility. The purpose of this study is to describe the effectiveness of psychological adjustment in elder siblings of a Down syndrome children. This research was done using narrative qualitative method by interviewing and observing four elder siblings' of children with Down syndrome. Each participants have different combinations of age-spacing with the Down syndrome children and number of siblings. The result shows some variety of effectiveness of psychological adjustment within each participants. The variety was caused by some individual factors, such as parents involvement and siblings' relationship quality.